Kinematics of the Pelvis, Torso, and Lower Limb During Obstacle Negotiation While Under Temporal Constraints - Christensen, Jesse C.; Wilson, Christopher R.; Merryweather, Andrew S.; Foreman, K. Bo (Anatomical record (Hoboken, N.J. : 2007), 2017)
ABSTRACT Biomechanics of unobstructed locomotion consists of synchronized complex movements of the pelvis, torso, and lower limbs. These movement patterns become more complex as individuals encounter obstacles or negotiate uneven terrain. To date, limited research has explored how specifically the pelvis, torso, and lower limb segments relate to obstacle negotiation of varying sized objects combined with temporal constraints to perform the task. Understanding pelvis and adjoining segment movements during object negotiation will provide necessary information in identifying abnormal mechanics and potential fall risk characteristics in balance compromised patient populations. In this prospective cohort study, we aimed to compare pelvic, torso, and lower limb kinematics during unobstructed locomotion with obstacle negotiation of varying heights. Ten healthy young adults (7 females and 3 males, mean age 28.4 ± 4.1 years, mean body mass index 22.5 ± 3.6 kg/m2) enrolled in this study. Analysis of within‐subject differences revealed a significant increase in sagittal (posterior tilt) and frontal (ipsilateral hike) plane pelvic angular displacement and higher sagittal plane posterior torso lean angular displacement with increased obstacle height. Furthermore, both sagittal plane hip and knee maximum joint flexion were significantly higher with increasing heights of the obstacles during negotiation. These data provide insight on segment mechanics within a non‐mobility‐impaired population; therefore, providing a baseline to understand the kinematic demands necessary for safe and effective gait in mobility‐compromised populations. Anat Rec, 300:732–738, 2017. © 2017 Wiley Periodicals, Inc.